Rüstungsindustrie im Kontext eines nachhaltigen Bankwesens – Finden Rüstungsunternehmen einen Platz im ESG-Universum? - Riegler, Markus; Reichel, Richard (List Forum für Wirtschafts- und Finanzpolitik, 2023)
This paper discusses the question of whether defense companies can find a place in the ESG universe, a question that has not yet been addressed in academic research. The current exclusion as a common practice as well as the proposals of the EU social taxonomy tighten the conditions of defense companies on the financial market. Due to current geopolitical conflicts and in the context of a worldwide re-armament, the question is addressed by means of qualitative content analysis according to Mayring with experts of the financial market, the armament industry as well as socio-ethical representatives. The experts confirm that defense and the defense industry are an aspect of security and that security is a basic condition for further sustainability efforts by societies, but that arms as such are rejected as a means of creating security in the ESG context, particularly by the financial market and society/ethics experts. These findings allow conclusions to be drawn about conditions as to how inclusion in the ESG universe would theoretically be possible, but also reveal rejecting, in some cases contradictory attributes from the expert perspective.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Defense industry; ESG; Sustainable banking; Sustainable investment